Exposure and health risks of livestock air resistomes - Wei Sun; Jun Wang; Guangdong Wang; Lan Jiang; Wenlu Feng; Shuangsuo Dang; Mei Li; Shuo Jiao; Gehong Wei; Jie Gu; James M. Tiedje; Xun Qian (Proceedings of the National Academy of Sciences, 2025)
Most of the global antibiotic consumption is by the livestock industry, making livestock farms a hotspot of antibiotic resistance genes (ARGs). Farm air poses direct ARG exposure to workers, but the health risks of air resistomes remain unclear. We evaluated the human exposure and health risks of air resistomes in pig and chicken farms and compared air resistomes in Chinese farms to those in European farms given their long-term restrictions on use of antibiotics in livestock. We found that livestock air was highly enriched in ARGs, with each cell harboring seven times more ARGs than urban air. The daily ARG inhalation of farm workers was equivalent to several years of ARG inhalation by urban residents. ARGs encoding resistance to last-resort antibiotics such as mcr-1 and tetX were detected in farm air, and tetX variants were prevalent in both Chinese and European farms. ARGs in livestock air were highly associated with mobile genetic elements, and conjugation experiments confirmed their cross-phyla transferability. The projected resistome risk of farm air was significantly higher than well-recognized ARG hotspots like air from hospitals, sewage treatment plants, and from animal manures. The diversity, abundance, and risk score of air resistomes in Chinese farms were significantly higher than those in European farms, suggesting that long-term restriction of antibiotic use mitigates antibiotic resistance in the livestock environment. Our results underscore the high exposure of farm workers to ARGs via farm air and highlight its role in ARG dissemination, supporting the importance of antibiotic stewardship practices in combating antibiotic resistance.